Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1080/10473289.2005.10464672
|View full text |Cite
|
Sign up to set email alerts
|

Surface Compositions of Carbon Sorbents Exposed to Simulated Low-Rank Coal Flue Gases

Abstract: Bench-scale testing of elemental mercury (Hg 0 ) sorption on selected activated carbon sorbents was conducted to develop a better understanding of the interaction among the sorbent, flue gas constituents, and Hg 0. The results of the fixed-bed testing under simulated lignite combustion flue gas composition for activated carbons showed some initial breakthrough followed by increased mercury (Hg) capture for up to ϳ4.8 hr. After breakthrough, the Hg in the effluent stream was primarily in an oxidized form (Ͼ90%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 10 publications
3
40
2
Order By: Relevance
“…Similar observations were also made in previous XPS studies of AC sorbents that also contained SO 2 and/or SO 3 in the flue gas. 13,14,32 The normalized amounts of S(VI) for the tested versus untested sorbents are as follows: 14.8% (TBP) vs 0.0% (UTBP), 5.0% (TSP) vs 0.4% (UTSP), and 1.5% (TSF) vs 0.7% (UTSF). Large increases in oxygen content accompanied the increase in the level of S(VI) species at a ratio of approximately 4:1, indicating that the S(VI) species formed during the capture process is SO 4 2− .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations were also made in previous XPS studies of AC sorbents that also contained SO 2 and/or SO 3 in the flue gas. 13,14,32 The normalized amounts of S(VI) for the tested versus untested sorbents are as follows: 14.8% (TBP) vs 0.0% (UTBP), 5.0% (TSP) vs 0.4% (UTSP), and 1.5% (TSF) vs 0.7% (UTSF). Large increases in oxygen content accompanied the increase in the level of S(VI) species at a ratio of approximately 4:1, indicating that the S(VI) species formed during the capture process is SO 4 2− .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To improve our understanding of how the capture of Hg by AC sorbents is related to acid gas concentrations in the flue gas, Olson et al 13 used X-ray photoelectron spectroscopy (XPS) to study the surface chemistry of AC in low-HCl (<200 ppm) simulated flue gas. Similar XPS studies were also performed on lignite AC by Laumb et al 14 and on brominated AC by Hutson et al 12 to understand the effect of flue gas components on the sorbent surface chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is partly due to the heterogeneous characteristics of the fly ashes and their generally low carbon content. When evaluating the role of carbon particles and the influence of gas composition, the interactions between the gas species and the surface of the activated carbons should be taken into account [19][20]. In combustion atmospheres, it has been observed that chlorine and sulfur species may be absorbed onto the surface of activated carbons and that these species may modify the surface and influence Hg retention [21].…”
Section: Because the Different Modes Of Occurrence Of Hg Involve Diffmentioning
confidence: 99%
“…Often a consequence of the use of low-NOx burners or low-NOx combustion systems, pulverized-coal boilers burning bituminous coal can produce high levels of unburned C, 5-30 wt% as loss-on-ignition (LOI) components. Mercury has been found to be concentrated in the C-rich fraction of fly ash [53][54][55]. Bituminous coal-ash produced under CESP conditions exhibits a consistent trend of increasing Hg removal with the unburned C content [56].…”
Section: Discussionmentioning
confidence: 93%